Induction of Siglec-FhiCD101hi eosinophils in the lungs following murine hookworm Nippostrongylus brasiliensis infection - Chetty, Alisha; Darby, Matthew G.; Pillaye, Jamie; Taliep, A'ishah; Cunningham, Adam F.; O’Shea, Matthew K.; Katawa, Gnatoulma; Layland, Laura E.; Ritter, Manuel; Horsnell, William G. C. (Frontiers in Immunology, 2023)
Helminth-induced eosinophils accumulate around the parasite at the site of infection, or in parasite-damaged tissues well after the helminth has left the site. The role of helminth-elicited eosinophils in mediating parasite control is complex. While they may contribute to direct parasite-killing and tissue repair, their involvement in long-term immunopathogenesis is a concern. In allergic Siglec-FhiCD101hi, eosinophils are associated with pathology. Research has not shown if equivalent subpopulations of eosinophils are a feature of helminth infection. In this study, we demonstrate that lung migration of rodent hookworm Nippostrongylus brasiliensis (Nb) results in a long-term expansion of distinct Siglec-FhiCD101hi eosinophil subpopulations. Nb-elevated eosinophil populations in the bone marrow and circulation did not present this phenotype. Siglec-FhiCD101hi lung eosinophils exhibited an activated morphology including nuclei hyper-segmentation and cytoplasm degranulation. Recruitment of ST2+ ILC2s and not CD4+ T cells to the lungs was associated with the expansion of Siglec-FhiCD101hi eosinophils. This data identifies a morphologically distinct and persistent subset of Siglec-FhiCD101hi lung eosinophils induced following Nb infection. These eosinophils may contribute to long-term pathology following helminth infection.